Social–Emotional Factors and Academic Outcomes Among Elementary‐Aged Children. Issue 2 (15th July 2015) - McKown, Clark; Russo‐Ponsaran, Nicole M.; Allen, Adelaide; Johnson, Jason K.; Warren‐Khot, Heather K.
Abstract : Social–emotional comprehension involves encoding, interpreting, and reasoning about social–emotional information, and self‐regulating. This study examined the mediating pathways through which social–emotional comprehension and social behaviour are related to academic outcomes in two ethnically and socioeconomically heterogeneous samples totaling 340 elementary‐aged children. In both samples, social–emotional comprehension, teacher report of social behaviour, and academic outcomes were measured in a single school year. In both samples, structural equation models showed that the relationship between social–emotional comprehension and reading was mediated by socially skilled behaviour. In one sample, but not the other, the relationship between social–emotional comprehension and math was mediated by socially skilled behaviour. This paper advances our understanding of the mechanisms through which social–emotional factors are associated with academic outcomes. Copyright © 2015 John Wiley & Sons, Ltd.